Use of Coronary Techniques in Celiac and Hepatic Artery Stenting in Post-Hepatic Transplant Patients - Harpreet Parmar; Ryan Beard; Mark W. Mewissen; Armaan Shaikh; Tanvir Bajwa (Journal of Patient-Centered Research and Reviews, 2015)
Hepatic artery stenosis (HAS) remains a rare but serious complication after liver transplantation. While invasive surgical techniques were needed for HAS treatment in the past, recently endovascular techniques, including hepatic artery stenting, have been proven to be a safe and effective treatment. The present work focused on a review of the recent literature regarding HAS as well as recent cases demonstrating the various presentations of HAS and the variety of approaches to endovascular intervention. Our single-center experience has shown endovascular treatment of HAS to be safe and effective, including the two specific cases discussed here. While further research is needed, endovascular stenting as a treatment for HAS appears to be a promising, minimally invasive technique to help aid in the long-term health of post-liver transplant patients.